In situ temperature measurements for selective epitaxy of GaN nanowires. Issue 3 (17th February 2014) - Bertness, Kris A.; Brubaker, Matt D.; Harvey, Todd E.; Duff, Shannon M.; Sanders, Aric W.; Sanford, Norman A.
Abstract: We demonstrate with spatially resolved, in situ temperature measurements and ex situ reflectance measurements that differences in appearance for masked and unmasked surfaces on patterned growth substrates arise from wavelength‐dependent emissivity variations and not from actual temperature differences. For this study, Si(111) substrates were coated with thin AlN buffer layers (about 40 nm thick) and then further coated with a SiNx mask layer (about 60 nm thick). "Blackbody" emission spectra were collected from homogeneous regions at growth temperatures near those that allow the selective epitaxy of catalyst‐free GaN nanowires on the AlN by molecular beam epitaxy. The data were acquired with a commercial in situ diagnostic system that incorporates optical fiber collection to limit the sampling area to a circle about 5 mm in diameter on the substrate. The emittance spectra are estimated from room‐temperature reflectance measurements. The implication for selectivity mechanisms and temperature measurements in molecular beam epitaxy in general are also discussed. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)